Global, Regional, and National Trends in Incidence and Mortality of Primary Liver Cancer and Its Underlying Etiologies from 1990 to 2019: Results from the Global Burden of Disease Study 2019 - Guiying Cao; Jue Liu; Min Liu (Springer, 2023)
Abstract Objective Primary liver cancer is not only one of the most common causes of cancer deaths but also the second most common cause of premature death worldwide. Understanding the trends in incidence and mortality of primary liver cancer and its etiologies is crucial for development of effective prevention and mitigation strategies. This study aimed to quantify the trends in incidence and mortality of primary liver cancer and its etiologies at the global, regional and national levels using data from Global Burden of Disease (GBD) study. Method Annual incident cases, deaths, age-standardized incidence rates (ASIRs), and age-standardized mortality rates (ASMRs) of primary liver cancer and its etiologies, including hepatitis B, hepatitis C, alcohol use, nonalcoholic steatohepatitis, and other causes, between 1990 and 2019 were collected from GBD study 2019. Percentage changes in incident cases and deaths and estimated annual percentage changes (EAPCs) in ASIRs and ASMRs of primary liver cancer and its etiologies were calculated to quantify their temporal trends. Correlations of EAPC in ASIRs and ASMRs with socio-demographic index (SDI) and universal health coverage index (UHCI) in 2019 were separately evaluated by Pearson correlation analyses. Results Globally, the incident cases and deaths of primary liver cancer increased by 43.11% from 373 393 in 1990 to 534 365 in 2019 and 32.68% from 365 213 in 1990 to 484 584 in 2019, respectively. ASIR and ASMR of primary liver cancer decreased by an average of 2.23% (95% CI 1.83%, 2.63%) and 1.93% (95% CI 1.55%, 2.31%) per year between 1990 and 2019 worldwide, respectively. ASIRs and ASMRs of primary liver cancer varied between regions, with an increasing trend in ASIR (EAPC = 0.91; 95% CI 0.47, 1.35) and a stable trend in ASMR (EAPC = 0.42, 95% CI − 0.01, 0.85) of primary liver cancer in high SDI region between 1990 and 2019. Nearly half (91/204) of the countries suffered an increasing trend in ASIR of primary liver cancer and more than one-third (71/204) of the countries suffered an increasing trend in ASIRs of primary liver cancer from all etiologies between 1990 and 2019 worldwide. Positive correlations of EAPC in ASIR and ASMR of primary liver cancer with SDI and UHCI were observed in nations with SDI ≥ 0.7 or UHCI ≥ 70. Conclusion Primary liver cancer remains a major public health concern globally, with an increasing trend in the numbers of incident cases and deaths in the past three decades. We observed an increasing trend in ASIR of primary liver cancer in nearly half of the countries and an increasing trend in ASIRs of primary liver cancer by etiology in more than one-third of the countries worldwide. In line with the Sustainable Development Goals, the identification and elimination of risk factors for primary liver cancer will be required to achieve a sustained reduction in liver cancer burden.